2002
DOI: 10.1021/jp013987f
|View full text |Cite
|
Sign up to set email alerts
|

Electron Hopping through Films of Arenethiolate Monolayer-Protected Gold Clusters

Abstract: Electron hopping in films of arenethiolate (benzylthiolate, phenylethylthiolate, phenylbutanethiolate, and cresolthiolate) monolayer-protected cluster molecules (MPCs) is investigated through measurements of solid-state electronic conductivity. Electron donor−acceptor hopping rates between the Au cores of arenethiolate MPCs exceed those of previously studied solid-state alkanethiolate MPC films, but the electronic coupling term, β = 0.8 Å-1, is nearly the same. Rate constants range from 108 to 1011 s-1 across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
150
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(166 citation statements)
references
References 48 publications
15
150
1
Order By: Relevance
“…The results of the first-order electron hopping rate constant, k ET ) of the arenethiolate capped-Au nanoparticle thin films. 58 This result supports the idea that the remaining long insulating OA, even after the ligand exchange process, limits the electron transfer in PbS-TAA QD solids.…”
Section: 1supporting
confidence: 76%
“…The results of the first-order electron hopping rate constant, k ET ) of the arenethiolate capped-Au nanoparticle thin films. 58 This result supports the idea that the remaining long insulating OA, even after the ligand exchange process, limits the electron transfer in PbS-TAA QD solids.…”
Section: 1supporting
confidence: 76%
“…Attempts have been made to explain E a with the "outer sphere" reorganization energy known from Marcus theory. [38] In another approach, E a was related to the classical Coulomb charging energy, which is required for transferring an electron from one electrically neutral particle to another. [5] In fact, experimental data for E a compare remarkably well with the expected Coulomb charging energies.…”
Section: N Krasteva Et Al/vapor Sorption Of Au Nanoparticle Compositesmentioning
confidence: 99%
“…In scanning tunneling spectroscopic (STS) studies of isolated particles, [1][2][3] the resulting currentpotential (I-V) profile generally exhibits a Coulomb blockade in the central region, beyond which a Coulomb staircase (single-electron transfer; SET) may be identified. Such unique characteristics are the fundamental basis for the development of single-electron transistors.[4] By contrast, in studies of nanoparticle ensembles that form (sub)micrometer-thick solid films, [5][6][7][8] typically only linear (Ohmic) I-V behavior is observed, especially at a relatively high voltage bias, because of rampant structural defects within these particle solids that facilitate interparticle charge transfer (e.g., percolation effects). Fundamentally, the collective conductivity properties of organized assemblies of particles are found to be determined not only by the particle chemical structure (core size, shape, and surface ligands), but by the specific chemical environments and interparticle interactions as well.…”
mentioning
confidence: 99%
“…The fact that we observed peaks instead of a staircase (as in STM measurements) can be ascribed to electron diffusion along the particle ensembles. Earlier studies of nanoparticles dispersed in polymer matrices and thick nanoparticle films [5,24] have shown that the charge migration (and hence conductance) is essentially limited by electron diffusion within the nanoparticle solids, akin to the case of redox-active polymer melts. Thus, the firstorder electron-hopping rate constant (k ET , s -1 ) can be calculated from the electron-diffusion coefficient (D EH ) (assuming a square lattice for the nanoparticle arrays, which is a rather reasonable approximation according to the STM measurements, see below) [5,24] [25] i P nFAD…”
mentioning
confidence: 99%
See 1 more Smart Citation